Taxonomic study of the cricket genus Valiatrella Gorochov (Gryllidae, Podoscirtinae) from China - Libin, Ma; Yalin, Zhang (Zootaxa, 2013)
Four Valiatrella species, Valiatrella pulchra (Gorochov, 1985), Valiatrella sororia (Gorochov, 2002), Valiatrella laminaria Liu & Shi, 2007 and Valiatrella multiprotubera Liu & Shi, 2007, recorded from China are reviewed. A new species, Val-iatrella persicifolius sp. nov., is described and illustrated.